Brexit negotiations: internal British context - N. A. Masnina (Проблемы постсоветского пространства)
The United Kingdom is set to officially leave the EU on 29 March 2019. However, London still doesn’t have a common strategy at the talks with Brussels, as well as a vision of an independent future of the country after the divorce. Amid this uncertainty, differences over the conditions of Brexit are currently on the rise both in the British society and the establishment. There is a significant increase in the number of people who are not satisfied with the Cabinet both in the opposition and among the Conservatives themselves, which undoubtedly threatens the governmental plan — Chequers. Die-hard eurosceptics, including former members of the Cabinet B. Johnson and D. Davis, urge not to make concessions to Brussels and to ensure autonomy of the UK in trade while maintaining the status quo on the Irish border. Those who are interested in business development support the idea of “soft Brexit” in order to keep getting benefits from access to the European free market. Moreover, some pro-European members of Parliament are still hoping to conduct another referendum. No progress is expected as a result of talks between the Secretary of State for exiting the EU Dominic Raab and his European counterpart Michel Barnier: Brussels continues to insist on creating a special economic zone in Northern Ireland without a hard border, which makes London fear possible alienation and another referendum. Regardless of the result of Brexit talks, internal political divisions will be increasing, jeopardizing Theresa May’s weak position as the Prime Minister and the leader of the Conservative Party. In an attempt to draw attention away from the negative consequences of Brexit in such a tense political situation, the British Prime Minister engages in multiple foreign-policy ventures, primarily anti-Russian rhetoric in the context of Syria, Ukraine and the Salisbury case. As a result, the UK has a destabilizing impact on world politics.